Metabolically controlled histone H4K5 acylation/acetylation ratio drives BRD4 genomic distribution - Gao, Mengqing; Wang, Jin; Rousseaux, Sophie; Tan, Minjia; Pan, Lulu; Peng, Lijun; Wang, Sisi; Xu, Wenqian; Ren, Jiayi; Liu, Yuanfang; Spinck, Martin; Barral, Sophie; et al. (Cell reports (Cambridge), 2021)
In addition to acetylation, histones are modified by a series of competing longer-chain acylations. Most of these acylation marks are enriched and co-exist with acetylation on active gene regulatory elements. Their seemingly redundant functions hinder our understanding of histone acylations’ specific roles. Here, by using an acute lymphoblastic leukemia (ALL) cell model and blasts from individuals with B-precusor ALL (B-ALL), we demonstrate a role of mitochondrial activity in controlling the histone acylation/acetylation ratio, especially at histone H4 lysine 5 (H4K5). An increase in the ratio of non-acetyl acylations (crotonylation or butyrylation) over acetylation on H4K5 weakens bromodomain containing protein 4 (BRD4) bromodomain-dependent chromatin interaction and enhances BRD4 nuclear mobility and availability for binding transcription start site regions of active genes. Our data suggest that the metabolism-driven control of the histone acetylation/longer-chain acylation(s) ratio could be a common mechanism regulating the bromodomain factors’ functional genomic distribution. [Display omitted] •Mitochondrial activity controls H4K5 acylation/acetylation ratio•H4K5 acylation/acetylation ratio fine-tunes BRD4-chromatin interactions•H4K5 acylation/acetylation ratio regulates BRD4 reservoir and functional pools•H4K5 non-acetyl acylations could be considered a single functional entity Gao et al. show that metabolically driven dynamic exchange between acylations and acetylation on histone H4K5 defines the stability of BRD4 interactions with chromatin. A high H4K5 acylation/acetylation ratio loosens BRD4 from its chromatin binding sites, increasing the pool of available BRD4 for recruitment on active TSS regions and transcriptional regulation.